Biophysical characterization and molecular docking studies of imidazolium based polyelectrolytes-DNA complexes: role of hydrophobicity - Manojkumar, Kasina; Charan, K. T. Prabhu; Sivaramakrishna, Akella; Jha, Prakash C.; Khedkar, Vijay M.; Siva, Ramamoorthy; Jayaraman, Gurunathan; Vijayakrishna, Kari (Biomacromolecules, 2015)
Nonviral gene delivery vectors are acquiring greater attention in the field of gene therapy by replacing the biological viral vectors. DNA-cationic polymer complexes are one of the most promising systems to find application in gene therapy. Hence, a complete insight of their biophysical characterization and binding energy profile is important in understanding the mechanism involved in nonviral gene therapy. In this investigation, the interaction between calf thymus DNA (ctDNA) and imidazolium-based poly(ionic liquids) (PILs) also known as polyelectrolytes with three different alkyl side chains (ethyl, butyl, and hexyl) in physiological conditions using various spectroscopic experiments with constant DNA concentration and varying polyelectrolyte concentrations is reported. UV-visible absorption, fluorescence quenching studies, gel electrophoresis, circular dichroism (CD), and Fourier transform infrared spectroscopy (FTIR) have confirmed the binding of polyelectrolytes with DNA. UV-vis absorption measurements and fluorescence quenching revealed that the binding between DNA and the polyelectrolyte is dominated by electrostatic interactions. Additionally, CD and FTIR results indicated that the DNA retained its B-form with minor perturbation in the phosphate backbone without significant change in the conformation of its base pairs. Preference for alkyl side chains (KPIL-Ethyl Br < KPIL-Butyl Br < KPIL-Hexyl Br) toward efficient binding between the polyelectrolyte and DNA was inferred from the binding and quenching constants calculated from the absorption and emission spectra, respectively. Further, in silico molecular docking studies not only validated the observed binding trend but also provided insight into the binding mode of the polyelectrolyte-DNA complex.